2021
DOI: 10.1055/s-0041-1741045
|View full text |Cite
|
Sign up to set email alerts
|

Study on Anatomical Variations in Fissures of Lung by CT Scan

Abstract: Introduction Refinements in the modern computed tomography (CT) imaging techniques have led to anatomical variations in the fissures of lung being diagnosed more frequently. So far, majority of the studies conducted are cadaveric. There is paucity of studies in this aspect based on chest CT images. Hence, we undertook this study to find the anatomical variations in the fissures. Prior detection of anatomical abnormalities is important to reduce postoperative complications in lung resection surgeries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
9
2
Order By: Relevance
“…In this study, we found anatomical variations in the pulmonary fissures in only 7.33% of patients which was lower than Manjunath et al (22.9%), Ranaweera et al (68.42%) and other parts of the world (Table 4 ) [ 2 , 9 , 11 - 16 ].…”
Section: Discussioncontrasting
confidence: 58%
See 4 more Smart Citations
“…In this study, we found anatomical variations in the pulmonary fissures in only 7.33% of patients which was lower than Manjunath et al (22.9%), Ranaweera et al (68.42%) and other parts of the world (Table 4 ) [ 2 , 9 , 11 - 16 ].…”
Section: Discussioncontrasting
confidence: 58%
“…Present study 7.33% fissure variations Manjunath et al [2] 22.9% fissure variations Ranaweera et al [16] 68.42% fissure variations Gebregziabher et al [12] 52.17% right complete oblique fissure 47.82% right incomplete oblique fissure Mpolokeng et al [9] 5.1% right complete oblique fissure 69.2% right incomplete oblique fissure Mutua et al [13] 63.16% right complete oblique fissure 36.84% right incomplete oblique fissure Mote et al [14] 83.4% right complete oblique fissure 16.6% right incomplete oblique fissure…”
Section: Variations Of Fissuresmentioning
confidence: 48%
See 3 more Smart Citations